Behavioural types for non-uniform memory accesses - Juliana Franco; Sophia Drossopoulou (Electronic Proceedings in Theoretical Computer Science, 2016)
Concurrent programs executing on NUMA architectures consist of concurrent entities (e.g. threads, actors) and data placed on different nodes. Execution of these concurrent entities often reads or updates states from remote nodes. The performance of such systems depends on the extent to which the concurrent entities can be executing in parallel, and on the amount of the remote reads and writes.